Alterações dermato-neurológicas relacionadas ao uso de capecitabina em pacientes com neoplasia do trato gastrointestinal - Canille, Rafaela Moreira da Silva (2019)
To evaluate the occurrence of hand-foot syndrome and peripheral neuropathy reactions induced by chemotherapy related to the use of Capecitabine in patients with neoplasia of the gastrointestinal tract. Casuistica and Methods: A descriptive, longitudinal, prospective study of a quantitative nature performed in a Chemotherapy Unit of a Quaternary Hospital in the interior of São Paulo state. Patients with neoplasia of the gastrointestinal tract, in a monotherapy treatment or combined therapy with Capecitabine participated in the study. They answered three instruments by means of interviews, being one of sociodemographic characterization, the instruments of Peripheral Neuropathy Induced by Chemotherapy and Visual Evaluation of Hand-Foot Syndrome. Data collection was performed from July 2016 to March 2017. Participants were interviewed for at least two cycles. Results: Out of the participants, 97.2% developed NPIQ and HFS. Both were predominant according to the CAPOX protocol, with 83.3% and 80.5%, respectively. Out of the participants, 94.4% developed grade 1. In relation to the sensitive symptoms, there was a predominance of sensitivity to cold, with 63.7%, and motor symptoms, weakness of MMSS and MMII were predominant. Conclusion: The study showed that the occurrence of hand-foot syndrome was incident in patients treated with Capecitabine, and the peripheral neuropathy induced by this drug is more frequent in combination therapy, mainly with Oxaliplatin. The symptoms caused by the side effects of antineoplastic drugs negatively affect the quality of life, impacting on the patients' performance status, leading to dose reduction and consequently reducing the therapeutic response.